El vasto gabinete del dr. Caligari (composición de grado y homenaje al mickey-mousing) (2021)
This musical composition (created as the final project for the academical emphasis on [Musical] Composition for Cinema & Media) consists in the creation of a soundtrack for a fragment of the expressionist film: The Cabinet of Dr. Caligari (1920). It's music is an experimental homage to the musical composition technique known as Mickey-Mousing.